Low expression of miR-29a is associated with aggressive biology and worse survival in gastric cancer - Yoshihisa Tokumaru (Nature Portfolio, 2021)
Abstract Advanced gastric cancer (GC) is one of the most lethal cancer types, thus a better understanding of its biology in patients is urgently needed. MicroRNA (miR)-29a is a known tumor suppressive miR that is related to metastasis, but its clinical relevance in GC remains ambiguous. Here, using a large GC patient cohort we hypothesized that low expression of miR-29a in GC is associated with aggressive cancer biology and worse survival. We demonstrated that low miR-29a GC enriched cell proliferation, apoptosis, metastasis, and angiogenesis related gene sets, as well as the higher expression of related genes. Low miR-29a GC was associated with less anti-cancer immune cell infiltration as well as immune related scoring. Low miR-29a GC demonstrated a worse overall survival (OS) as well as disease specific survival (DSS) compared with high expressing miR-29a GC. Notably, low miR-29a expression was the only factor, other than residual tumor status, to be an independent prognostic biomarker of worse OS and DSS. In conclusion, low miR-29a GC was associated with aggressive cancer biology and worse OS as well as DSS. Additionally, low expression of miR-29a was an independent prognostic biomarker of OS and DSS in gastric cancer patients.